Morphological variation and sex dimorphism in adult Аzov Yellow-legged Gull Larus cachinnans сachinnans - Neubauer, G.; Koshelev, A.I.; Koshelev, V.A.; Zagalska, M. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 2001)
Gulls were trapped in the breeding colony on islands of Molochny Liman, a salt reservoir near the north Azov seashore (south of Zaporizhzhia Region, Ukraine). The total of measured cachinnans is 80 birds, more than 3500 nestlings were ringed. For trapped birds a total of 28 parameters were taken (14 metrical and 14 colour features). Blood samples were obtained from the most of the captured birds for further genetical analysis, and pictures were taken to record coloration (colour of eyes, legs, mantle, etc.).